Infection situatus of parasites in freshwater fishs collected in Lam river, Do Luong district, Nghe An province - Duc, Nguyen Van; Binh, Tran Thi; Hung, Nguyen Manh; Hien, Hoang Van (Academia Journal of Biology, 2012)
The results obtained from our research about the parasitic worm, which parasitized freshwater fishs of Lam river (Do Luong district, Nghe An province) provide us the basic knowledge about parasites of freshwater fishs in North Central Vietnam. Total 217 individuals of freshwater fish were carried out an autopsy for checking fish parasites. Among them, 118 fishes (occupied 54.4% total number of surgical fish) belonged to 13 species of Cypriniformes (occupied 54.2% total number of fish species). Of the total 832 samples of fish parasites collected, there were 504 samples of Monogenea, 212 Trematodes, 25 Cestodes, 16 Acanthocephala, 44 Nematoda and 31 Copepoda. Infected rate of fish in study site was not too high, the prevalence was 39.2%. and the density of parasites per each infected host was 9,8 individuals/host. Monogenea was the highest infected group (26.3%), while other groups were lower: from 1.4% to 7.4%. The infected rate was highest in cranoglanis 90%, the next was hemicultus 54.5%, tilapia 50%, red - eyed carp and major carp 40%, mudfish 28.0%. In case of 14 fish species, with 10 surgical fish individuals, the infection rate fluctuated between 16.7% and 90%. The infected rate was observed as the highest in Cranoglanis sinensis (90%) and the lowest in Tilapia (16.7%). Parasite infection intensity in not too high, one individual of fish infected with 9.8 worms in average (min - max: 1 - 84). The highest infected intensity was found in common carp 33.0 worms/fish (1 - 64), the next is red - eyed carp 29.0worm/fish and cranoglanis 13.9worms/fish; the lowest infection intensity was found in hemicultur 12.3 worms/fish. The certain host are normally infected with 2 or 3 parasite groups their prevalence and density is not too high.